Where Does Maladministration End and Corruption Begin? Delineating the Constitutional Boundary After Indonesian Constitutional Court Decision No. 66/PUU-XXIV/2026: A Fiqh Siyasah Perspective - Syurpana Nofanda (LaKaspia, 2026)
This study examines the line of demarcation between maladministration and criminal corruption following the issuance of Constitutional Court Decision Number 66/PUU-XXIV/2026, utilizing the Chromebook procurement case at the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) for the 2020–2022 fiscal period as its primary object of study. Employing a normative legal research method combining statutory, conceptual, and case approaches, this study's novelty lies in the construction of a Four-Dimensional Demarcation Model that systematically tests concrete cases using four cumulative parameters: (1) presence of mens rea; (2) existence of personal/third-party benefit; (3) proven actual financial loss; and (4) failure of administrative corrective mechanisms. Findings reveal that the Constitutional Court's decision establishes clearer quantitative parameters by aligning the phrase 'state loss' (kerugian negara) with 'state financial loss' (kerugian keuangan negara) in Article 20 paragraphs (5) and (6) of Law No. 30 of 2014, while potentially narrowing the corrective function of administrative law. Application of the demarcation model to the Chromebook case confirms that all four parameters are cumulatively satisfied, legally justifying the transformation from maladministration to criminal corruption. Nonetheless, this study criticizes the absence of a mandatory pre-judicial APIP assessment gateway prior to criminal investigation. Furthermore, this study highlights the relevance of the Islamic principles of amanah (trustworthiness) and hisbah (supervisory oversight) in fiqh siyasah as a normative foundation convergent with the administrative-first ethos embedded in Constitutional Court Decision No. 66/PUU-XXIV/2026. The study recommends enacting implementing regulations for Constitutional Court Decision No. 66/PUU-XXIV/2026 that establish a mandatory administrative gateway and standardize state loss audit methodologies.